Thermal radiation effect on MHD nanofluid flow with viscous dissipation - J. Barik; Sahoo, S. N.; Mishra, S. R. (Journal of Naval Architecture and Marine Engineering, 2024)
Recent advances in technology basically need enhanced thermal properties and this can be achieved by the use of nanoparticles. The inclusion of particle concentration in the base fluid augments the thermal conductivity which is useful in several areas of industries and engineering. Particularly, for the cooling of electronic devices, the drug delivery processes, peristaltic pumping processes, etc. The present investigation addresses the effect of thermal radiation on MHD nanofluid flow with viscous as well as Joule dissipation past over an expanding surface. The basic governing equations of the flow are converted into ordinary differential equations using stream function and similarity variable. The reduced nonlinear ODEs are solved numerically with MATLAB’s built-in solver bvp4c. The parametric behavior on the flow phenomena is presented through graphs and described briefly. Some of the important findings are deployed as; Due to the higher conductivity of silver nanoparticles compared to copper, the temperature distribution in Ag-water nanofluid is greater than in Cu-water nanofluid. An increase in the thermal radiation parameter reduces the gap between the thermal boundary layers. The onset of Lorentz force increases the skin friction coefficient more rapidly in Cu-water nanofluid than in Ag-water nanofluid. Journal of Naval Architecture and Marine Engineering, 21(2), 2024, P: 183- 193